Impact Of Social Media Marketing On Brand Image On Purchase Decisions Of Millenials Consumers - Hastuti Hastuti (Penerbit Jurnal Indonesia, 2021)
Social media marketing has a substantial and beneficial influence on brand image. Cosmetics are becoming increasingly popular among the millennial age, particularly in major cities. Previous study has found that millennials are highly worried about how others view them. Consumption of goods via online or social media is one of the qualities that might aid in the development of their identity. The goal of this study was to determine the impact of social media marketing on brand image, cosmetic purchasing decisions among millennial consumers, and the relationship between emotional aspects (self-concept connection, brand love, and emotional attachment) and brand loyalty on consumer willingness to buy Nu Skin cosmetic products. The conceptual model established in this study was evaluated in actual investigations after a review of the literature to identify gaps from prior research. Previous research was used to modify the instrument. According to the findings of this study, the influence of social media marketing on brand image has the biggest impact on cosmetic customers' brand loyalty (Nu Skin). Loyalty has shifted from a single brand to a younger consumer lifestyle when it comes to purchasing cosmetics (Nu Skin). Despite the fact that the study sample should be increased, these findings aid brand managers in establishing successful brand strategies that will secure the company's long-term viability